Synthesis and review: African environmental processes and water-cycle dynamics - Charles Ichoku; Jimmy Adegoke (Environmental Research Letters, 2016)
Africa’s vast landmass harbors a variety of physical processes that affect the environment and the water cycle. This focus issue on ‘African Environmental Processes and Water-Cycle Dynamics’ contains eight articles that address these phenomena from different but complementary perspectives. Fires used for agricultural and related purposes play a major role in land-cover change, surface albedo modifications, and smoke emission; all of which affect the environment and the water cycle in different ways. However, emissions of aerosols and trace gases are not restricted to fires, but also emanate from other natural and human activities. The African water cycle undergoes significant perturbations that are attributable to several factors, including the aforesaid environmental processes. These changes in the water cycle have produced severe drought and flooding events in recent decades that affect societal wellbeing across sub-Saharan Africa. The combined effects of the environmental processes and water-cycle dynamics affect and are affected by climate variability and can be propagated beyond the continent. Future studies should utilize the wealth of observations and modeling tools that are constantly improving to clearly elucidate the interrelationships between all of these phenomena for the benefit of society.